The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/2017ja024379
|View full text |Cite
|
Sign up to set email alerts
|

On the Relation Between Soft Electron Precipitations in the Cusp Region and Solar Wind Coupling Functions

Abstract: In this study, the correlations between the fluxes of precipitating soft electrons in the cusp region and solar wind coupling functions are investigated utilizing the Lyon‐Fedder‐Mobarry global magnetosphere model simulations. We conduct two simulation runs during periods from 20 March 2008 to 16 April 2008 and from 15 to 24 December 2014, which are referred as “Equinox Case” and “Solstice Case,” respectively. The simulation results of Equinox Case show that the plasma number density in the high‐latitude cusp … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…In support of the former, the simulation results of Damiano et al (2010) showed that increases in SW P lead to increased cusp electron precipitation, which effectively enhances the available supply of upflowing ions for outflow. Dang et al (2018) reported simulation results that implicate the solar wind pressure as the most important controlling factor of both the hemispheric precipitation rate and the hemispheric power of precipitating soft electrons in the cusp proper. A strong correlation between densities in the cusp and solar wind density was reported by Walsh et al (2016), which presents indirect observational evidence of a connection with SW P .…”
Section: Occurrence and Density Dependencies On Solar Wind Pressurementioning
confidence: 99%
See 1 more Smart Citation
“…In support of the former, the simulation results of Damiano et al (2010) showed that increases in SW P lead to increased cusp electron precipitation, which effectively enhances the available supply of upflowing ions for outflow. Dang et al (2018) reported simulation results that implicate the solar wind pressure as the most important controlling factor of both the hemispheric precipitation rate and the hemispheric power of precipitating soft electrons in the cusp proper. A strong correlation between densities in the cusp and solar wind density was reported by Walsh et al (2016), which presents indirect observational evidence of a connection with SW P .…”
Section: Occurrence and Density Dependencies On Solar Wind Pressurementioning
confidence: 99%
“…Dang et al. ( 2018 ) reported simulation results that implicate the solar wind pressure as the most important controlling factor of both the hemispheric precipitation rate and the hemispheric power of precipitating soft electrons in the cusp proper. A strong correlation between densities in the cusp and solar wind density was reported by Walsh et al.…”
Section: Statisticsmentioning
confidence: 99%
“…Based on high‐resolution Thermosphere Ionosphere Electrodynamics General Circulation Model (TIEGCM) simulations as well as on DMSP satellite observations,Dang T et al (2019) have reported the occurrence of double Tongues of Ionization (TOIs) (Figure 11) and carried out a comprehensive study of the dynamic evolution and formation mechanism of double TOIs. Predicting the cusp electron precipitation is important in investigating the dayside solar wind‐magnetosphere–ionosphere coupling process and in forecasting space weather phenomena Dang T et al (2018c). used the global MHD simulation to investigate the correlation between the fluxes of precipitating electrons in the cusp and the upstream solar wind conditions.…”
Section: Ionospheric Dynamics and Couplingsmentioning
confidence: 99%